One Christ—Many Witnesses: Visions of Mission and Unity, Edinburgh and Beyond - Robert, Dana Lee (Transformation, 2016)
This paper surveys the relationship between mission and Christian unity from the Edinburgh 1910 conference to the present. It then identifies several factors that cohere in recent missiological reflection, and concludes with a scriptural model for our contemporary pilgrimage together.